Lupus Need to Know - Hamdy Mohammed, Reem A. (Rheumatology, 2021)
Systemic lupus erythematosus (SLE) is a multisystem, immune-mediated, inflammatory disease of unknown etiology. It is difficult to diagnose and thus effective intervention in SLE patients is often delayed. This book is a comprehensive guide to lupus, with chapters on diagnosis, assessment, treatment, the link between lupus and endocrinopathies, lupus and pregnancy, and advances in therapeutics. The book is presented by devoted authors who sought the latest evidence-based data to provide a well-structured display aiming at setting standards for best practice guidelines in the diagnosis and management of each and every section discussed in the "Lupus- Need to Know."